Write a Scientific Paper (WASP) - what can I publish (2)? Hierarchies of evidence. (February 2019) - Cuschieri, Sarah; Grech, Victor
Abstract: Evidence-based published data is the prime source used for clinical decision making, the issuance of guidelines and the drafting new policies. A number of different study designs are used to perform and publish research studies, corresponding to the research question being investigated. Over the decades, a hierarchical system of evidence has been established. This provides an indication of the level of evidence each study design contributes to the research community. Policies and clinical guidelines should naturally be based on the highest level of evidence data available. However, the highest level of evidence study designs may not always provide an adequate answer to a research question. Thus, when utilising published evidence-based data, one should first understand the clinical question that needs to be answered, and then critically appraise the published data accordingly.